2008
DOI: 10.1353/pla.0.0007
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Performance Systems, Library Instruction, and Instructional Design: A Pilot Study

Abstract: To explore how effective CPS (Classroom Performance Systems) are in the classroom, specifically for library instruction, this pilot study considered the question: “Does the use of CPS improve student retention of information presented in class as measured by pre-and posttest scores?” The use of pretest and posttest measurements for the retention of information attempted to assess the impact of instruction using CPS for a single session and the usefulness of CPS for the delivery of instruction, generally. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Results indicated that both groups showed improved scores between the pre-and posttests. However, Petersohn (2008) reported statistically significant differences between the clicker and nonclicker groups; specifically the clicker group showed more improvement than the nonclicker group; however, generalization of these findings is limited because of the small number of participants.…”
Section: Library Instructionmentioning
confidence: 90%
See 2 more Smart Citations
“…Results indicated that both groups showed improved scores between the pre-and posttests. However, Petersohn (2008) reported statistically significant differences between the clicker and nonclicker groups; specifically the clicker group showed more improvement than the nonclicker group; however, generalization of these findings is limited because of the small number of participants.…”
Section: Library Instructionmentioning
confidence: 90%
“…Although Hoffman and Goodwin (2007) reported positive results from applying response systems during library-related instruction, there are few hard data on how effective information literacy classes are in teaching library literacy skills using this method (Petersohn, 2008). Petersohn (2008) conducted a pilot study to assess the impact of response systems during library instruction on short-term retention.…”
Section: Library Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a survey of academic librarians, Connor (2009) agrees that the use of clickers can prompt greater classroom interactivity through an assessment of students' understanding of IL concepts. Petersohn (2008) proposes clickers as classroom management devices with the potential to reduce off-task behavior during one-shot sessions. Hoffman and Goodwin (2006) explore the relationship between student enjoyment of the PRS devices and an increase in class participation and discussion.…”
Section: Clickers and Library Instructionmentioning
confidence: 99%
“…Using pre-and post-tests, Petersohn (2008) finds that clicker classes show higher post-test achievement. However, Dill (2008) concludes that although students are more engaged in PRS classes, their quiz results do not demonstrate greater information retention.…”
Section: Clickers and Library Instructionmentioning
confidence: 99%